2015
DOI: 10.1017/s0950268815001211
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of risk factors for death from 2009 pandemic influenza A(H1N1): is American Indian racial status an independent risk factor?

Abstract: Summary Historically, American Indian/Alaska Native populations (AI/AN) have suffered excess morbidity and mortality from influenza. We investigated the risk factors for death from 2009 pandemic influenza A (H1N1) among persons residing in five states with substantial AI/AN populations. We conducted a case-control investigation using pandemic influenza fatalities from 2009 in Alaska, Arizona, New Mexico, Oklahoma and Wyoming. Controls were outpatients with influenza. We reviewed medical records and interviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 27 publications
5
49
0
1
Order By: Relevance
“…Smoking history was another pedictor of FluA-p mortality in our study, which is a finding commensurate with some previous reports [34][35][36]. Wong and colleagues, for example, found that influenza-related mortality for all-causes and for cardiovascular and respiratory diseases was greater in current and exsmokers than in never smokers [34].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Smoking history was another pedictor of FluA-p mortality in our study, which is a finding commensurate with some previous reports [34][35][36]. Wong and colleagues, for example, found that influenza-related mortality for all-causes and for cardiovascular and respiratory diseases was greater in current and exsmokers than in never smokers [34].…”
Section: Discussionsupporting
confidence: 93%
“…Early administration of NAI therapy is associated with better outcomes in severe influenza [40,41]. Old age, obesity, pregnancy and chronic medical conditions, such as COPD, diabetes mellitus, and chronic kidney disease, have been associated with poorer outcomes in patients with influenza [35,42,43]. However, in our study only cardiovascular disease was identified as a risk factor for mortality in FluA-p patients.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Smoking history was another pedictor of FluA-p mortality in our study, which is a finding commensurate with some previous reports [35][36][37]. Wong and colleagues, for example, found that influenza-related mortality for all-causes and for cardiovascular and respiratory diseases was greater in current and ex-smokers than in never smokers [35].…”
Section: Psi and Curb-65 Scores Are Recommended By The Infectious Dissupporting
confidence: 93%